Efeito da superfície de parafusos ortopédicos na adesão e formação de biofilme de Staphylococcus aureus - Libardoni, Renato do Nascimento (2022)
One of the most feared and challenging complications in the treatment of patients with musculoskeletal trauma is implant-associated infection (IAI), considered common and serious in orthopedics and includes infection after fracture fixation (IAFF) and infection of the prosthetic joint, resulting from bacterial colonization and biofilm formation on the implanted device and infection of adjacent tissues by microorganisms such as S. aureus. Based on the relevance of these themes, this thesis was elaborated with two scientific articles. In Chapter 1, the adhesion profile and biofilm formation of Staphylococcus aureus on stainless steel (ASTM F138 alloy) and titanium (Ti-6Al-4V alloy) orthopedic screws were evaluated, using the dynamic method, in order to identify the best surface. There was adhesion and biofilm formation of S. aureus on both surfaces, with no significant difference (p > 0.05) between the groups at the times evaluated. In Chapter 2, silver ion implantation was performed at low energies in stainless steel (ASTM F138 alloy) and titanium (Ti-6Al-4V alloy) orthopedic screws and to evaluate the effect of this surface modification on adhesion and biofilm formation of Staphylococcus aureus. In this study, two experiments were performed. In experiment I, silver was implanted in stainless steel screws (ASTM F138 alloy) using energies of 2 keV and 4 keV. S. aureus adhesion and biofilm formation assays were performed using the static method. There was adhesion and biofilm formation of S. aureus on the surface of the screws, with and without implantation of silver ions. The results showed a significant difference (p=0.031) in S. aureus biofilm formation at 96 hours between Ag2/F138 (6.19 log10.CFU.cm-2) and Ag4/F138 (5.63 log10. CFU.cm-2). In experiment II, silver was implanted in stainless steel screws (ASTM F138 alloy) and titanium (Ti-6Al-4V alloy) using energies of 6 keV and 8 keV. S. aureus adhesion and biofilm formation assays were performed using the static method. There was a difference (p=0.026) in S. aureus biofilm formation at 1 hour between the C/Ti (2.18 log10.CFU.cm-2) and Ag8/Ti (1.92 log10.CFU.cm-2) groups. We conclude that surface modification of stainless steel and titanium orthopedic screws by implanting silver ions at low energies was not able to promote an acceptable antibacterial effect. Our results are important as many devices have been subjected to studies to determine resistance to infection. It is from these studies that the design features of a fracture fixation device that make it more or less susceptible to contamination are identified.